Essential Oil Bioactive Fibrous Membranes Prepared via Coaxial Electrospinning - Yao, Zhi‐Cheng; Chen, Si‐Cong; Ahmad, Zeeshan; Huang, Jie; Chang, Ming‐Wei; Li, Jing‐Song (Journal of food science, 2017)
A novel antimicrobial composite material was prepared by encapsulating orange essential oil (OEO) in zein prolamine (ZP) via the coaxial electrospinning (ES) technique. By manipulating process parameters, the morphological features of ZP/OEO fibers were modulated. Fine fibers with diameters ranging from 0.7 to 2.3 μm were obtained by regulating ZP solution concentration and process parameters during the ES process. Optimal loading capacity (LC) and encapsulation efficiency (EE) of OEO in fibrous ZP mats were determined to be 22.28% and 53.68%, respectively, and were achieved using a 35 w/v% ZP ES solution. The encapsulation of OEO was found to be reliant on ZP solution concentration (the enveloping medium). SEM analysis indicates the surface morphology of ZP/OEO electrospun fibers is dependent on ZP solution loading volume, with lower ZP concentrations yielding defective fibrous structures (for example, beaded and spindled‐string like morphologies). Furthermore, this loading volume also influences OEO LC, EE, mat water contact angle and oil retention. CCK‐8 assay and cell morphology assessment (HEK293T cells) indicate no significant change with electrospun ZP and ZP/OEO fibrous membranes over an 8 h period. Antimicrobial activity assessment using Escherichia coli, suggests composite nonwovens possess sterilization properties; elucidating potential application in active food packaging, food preservation and therefore sustainability. Practical Application Composite ZP/OEO fibrous membranes, fabricated using coaxial electrospinning technique, exhibit nontoxic in vitro behavior and antimicrobial potential. This indicates their potential application for bioactive food packaging improving sustainability.